Humanized chimeric mouse models of hepatitis B virus infection. (June 2017) - Sun, Suwan; Li, Jun
Abstract: Hepatitis B virus (HBV) infection is associated with an increased risk of hepatic cirrhosis, hepatocellular carcinoma, fulminant hepatitis and end-stage hepatic failure. Despite the availability of anti-HBV therapies, HBV infection remains a major global public health problem. Developing an ideal animal model of HBV infection to clarify the details of the HBV replication process, the viral life cycle, the resulting immunoresponse and the precise pathogenesis of HBV is difficult because HBV has an extremely narrow host range and almost exclusively infects humans. In this review, we summarize and evaluate animal models available for studying HBV infection, especially focusing on humanized chimeric mouse models, and we discuss future development trends regarding immunocompetent humanized mouse models that can delineate the natural history and immunopathophysiology of HBV infection. Highlights: The immune response plays a critical role in HBV clearance and pathogenesis. Developing dual humanized mice is needed to model natural history of HBV infection. Stem cells transplantation may useful to develop dual humanized mice.